FACTORS AFFECTING THE FORMATION ARCHITECTURAL PLANNING AND FUNCTIONAL AND SPATIAL ORGANIZATION OF THE TRAINING BASES FOOTBALL CLUB - and (Municipal economy of cities. Series: «Economy science», 2013)
To Euro 2012 as part of the overall infrastructure necessary to build new and renovate existing training base Football Clubs of Ukraine. The study identified the main factors that influence the architecture and planning and functional spatial organization of training bases football clubs.